PERLINDUNGAN HUKUM TERHADAP HAK ANAK JALANAN YANG TERLANTAR TANPA ADANYA KETERLIBATAN PERAN ORANG TUA DALAM SISTEM HUKUM NASIONAL - Ramlin Ahmad; Heli Komarudin; Alexander Satria Aji Wibowo (Universitas Kapuas, 2026)
Children are legal subjects whose rights must be protected by the state, particularly in the absence of parental care. In Indonesia, neglected street children remain vulnerable to exploitation, violence, and deprivation of basic rights. Law Number 35 of 2014 classifies such children as neglected and entitled to special protection. This study employs a normative juridical method by analyzing statutory regulations, legal principles, and relevant legal materials, focusing on the state’s responsibility and the effectiveness of protection. The findings show that Indonesia’s legal framework normatively provides adequate protection through constitutional provisions, child protection laws, and international commitments. However, implementation remains ineffective due to weak coordination, limited facilities, low legal awareness, and weak law enforcement. Strengthening an integrated, child-centered protection system is necessary to ensure effective and sustainable protection.